Development of Occupational Safety and Health Guidelines Using Quick Response Code on Land Measuring Tools for Students Vocational - Muhammad Nur Fuad; Rini Kusumawardani; Eko Supraptono; Yeri Sutopo; Sri Handayani (Universitas Ahmad Dahlan, 2026)
In 2023, Indonesia recorded 370,747 work accident cases across various sectors, with the construction sector contributing the highest percentage at 40%. Many accidents are caused by limited understanding and low compliance with Occupational Safety and Health (OSH) procedures. Improving OSH understanding can be achieved through education, especially in vocational schools. SMK Negeri 3 Semarang has implemented an independent curriculum with a teaching factory system, but there is still no systematic OSH guide for soil measurement learning. Therefore, this study aims to develop a more structured and innovative QR Code-assisted OSH guide for soil measurement.This research used the Research and Development (R&D) method with the ADDIE model. The sample consisted of 70 Phase E students from the Construction and Housing Engineering program. Data analysis included validation by material experts and media experts to determine feasibility, practicality tests through teacher and student questionnaires, and effectiveness tests using pretest and posttest results. The data were first tested for normality and homogeneity before being analyzed using the T-Test and N-Gain test. The results showed that both material and media expert validations reached 91%, while the practicality test scored 92%. The effectiveness test produced an N-Gain score of 79%, categorized as effective. These findings indicate that the QR Code-assisted soil measurement OSH guide is feasible, practical, and effective in improving students’ understanding and implementation of OSH procedures.